Fetal Ductal Constriction due to Maternal Intake of Metamizole - Bermejo, Rosa; Naiara, Pérez de Heredia; Sanchez-Ferrer, Francisco; Quereda, Francisco (Archives of Case Reports, 2023)
The prevalence of intra-uterine dysfunction of ductus arteriosus is unknown and the clinical consequences are poorly understood. We report a case of prenatal diagnosis of premature closure of the ductus arteriosus due to maternal intake of metamizole during pregnancy. Fetal echocardiography at 37 weeks of gestation revealed a right ventricular hypertrophy and suspected stenosis of the tricuspid valve. A cesarean section led to an excellent neonatal outcome. The aim of this report is to show echocardiographic abnormalities and outcomes of this rare phenomenom.